Arsen Rychinsky as a scholar and polemicist - Yarotskiy, Petro (Ukrai͏̈ns'ke relihijeznavstvo, 2007)
In a number of the author's scientific religious studies, A. Richinsky appears as a deep researcher of the history of Christianity and, in particular, of the history of Ukrainian Christianity. In controversy with his opponents, he attests to a thorough knowledge of the process of forming Christian dogmas of church canons, biblical texts, which he convincingly and skillfully operates as a professional exegete. At the same time, A. Richinsky appears to us as a tolerant, ecumenical personality, not inclined to religious confession, bias towards "non-believers", free from religious fanaticism and clerical extremism. If such a figure were today among our Ukrainian intelligentsia or, better yet, among the Orthodox hierarchy, the cause of unification of all Ukrainian Orthodox churches would inevitably have come to a standstill.